Entartung - Nordau, Max Simon, 1849-1923 (Europäisch-jüdische Studien. Editionen., 2013)
In a new edition, Karin Tebben presents Nordau's best-known work "Degeneration" ("Entartung," 1892/93), which focuses on the modern pathologies of artistic modernism. Together with Nietzsche, Nordau is one of the most influential thought leaders of a tradition that, as it developed further, had a problematic influence not only on the National Socialist organizers of the book burnings and of the "Entartete Kunst" (Degenerate Art) exhibition of 1937, but also on the Bolshevist persecution of the artistic modern or on Georg Lukács' polemic against the avant-garde modern.